Application of the Right to Permanent Sovereignty over Natural Resources to Indigenous Peoples: Assessment of current legal developments - Enyew, Endalew Lijalem (Arctic Review on Law and Politics, 2017)
The right to Permanent Sovereignty over Natural Resources (PSNR) emerged in the era of decolonization. As a reaction to the irresponsible exploitation of their natural resources by colonial powers, the peoples under colonial rule and the newly independent developing states asserted the right to control and dispose of their own natural resources. The UN General Assembly recognized and reinforced their claims by adopting series of resolutions relating to the right of PSNR so as to facilitate the process of decolonization. However, the subjects of the right to PSNR has expanded to include ‘all peoples’ due to legal developments in international law pertaining to the right to self-determination of peoples and other human rights standards. This article explores the contemporary application of the right to PSNR to indigenous peoples, by virtue of their being of ‘peoples’, tracing the various developments in the international law of indigenous peoples since the inception of the right in the 1950s.